DESAIN LANSKAP PERTANIAN TERPADU SEBAGAI WAHANA PENDIDIKAN DAN WISATA PERTANIAN - Eduwin Eko Franjaya; Andi Gunawan; Wahju Qamara Mugnisjah (Jurnal Lanskap Indonesia, 2013)
ABSTRACTAgriculture is the one of the important sector that contributes the economic growth in Indonesia. But, now the economic growth is not in line with the agricultural land growth and the prosperity of the farmer. The effort to develop the agricultural sector which engage the farmer is the one thing that we can do to increase the prosperity of the farmer. Integrated farming give us the big opportunity to increase the farmer’s income in the village. Basically, the integrated farming is the agricultural system which characterized with the interaction and synergy dependability between various agricultural activities. The methode of this research is descriptive methode, using various reference books to get information about integrated farming. Then, applying the information to concept and concept development. Activity base is the main concept of this research, and the result of this research is integrated farming landscape.Keywords : agricultural landscape, agricultural tourism, desain, education, integrated farming